The Impact of Smoking on Clinical Outcomes after Percutaneous Coronary Intervention in Women Compared to Men - Seyyed Saeed Mohammadi; Mohammad Javad Zibaeenezhad; Mehrab Sayadi; Soorena Khorshidi; Ehsan Hadiyan; Iman Razeghian-Jahromi (Journal of Interventional Cardiology)
Background. For decades, cardiovascular diseases (CVD) have been known as men’s disease. However, recent research studies showed that they have become more common in women. Smoking is a strong risk factor for CVD especially that of coronary artery disease (CAD). Several studies reported that women are more susceptible to drastic sequels of smoking than men. There is limited data regarding the impact of smoking on post-revascularization clinical events stratified by gender. This study aimed to investigate if gender significantly changes the incidence of adverse clinical outcomes after percutaneous coronary intervention (PCI) among those with history of smoking. Methods. Participants were selected from two hospitals from 2003 to 2019. Among patients who had PCI (index PCI), those with stable CAD who underwent elective PCI were included. Exclusion criteria were defined as primary PCI and those with multiple prior revascularizations. Participants were followed up seeking for major adverse cardiac events (MACE) including revascularization (PCI or coronary artery bypass grafting), myocardial infarction, and coronary death in three time intervals according to the time of index PCI (short term: up to 24 hours, mid-term: 24 hours to less than 6 months, and long term: more than 6 months). Results. Of the 1799 patients, 61% were men and 47.08% had history of smoking (75% of the smokers were men). At the time of index PCI, smokers were significantly younger than nonsmokers. Also, MACE were significantly higher in smokers than nonsmokers, which was particularly pronounced at the long-term interval. In the nonsmokers group, there was no difference in MACE occurrence between men and women. However, of the smokers, women showed significantly higher MACE rate compared with men peers. Conclusion. Smoking makes women more prone to MACE in comparison to men among patients with stable CAD after PCI with drug-eluting stent.